2022
DOI: 10.12688/f1000research.76187.2
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer activity of Caesalpinia sappan by downregulating mitochondrial genes in A549 lung cancer cell line

Abstract: Background: The standardization and mechanism of action of Caesalpinia sappan as an anticancer agent are still lacking. This study aimed to understand the mechanism of action of  C,sappan extract as an anticancer agent. Methods: This study was conducted using the A549 lung cancer cell line to understand the mechanism of action of C. sappan extract as an anticancer agent. The cytotoxicity activity, cell cycle progression, apoptosis, protein-related apoptosis (i.e., BCL-2and BAX protein) assays, and RNA sequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Study demonstrated that C. sappan extract can inhibit cancer cell growth by inducing apoptosis and mitochondrial dysfunction in A549 cells ( Widodo et al, 2022 ). The effect of 3-deoxysappanchalcone (273) on colon cancer cell growth revealed its inhibitory potential on the activity of T-lymphokine-activated killer cell-originated protein kinase (TOPK).…”
Section: Pharmacologymentioning
confidence: 99%
“…Study demonstrated that C. sappan extract can inhibit cancer cell growth by inducing apoptosis and mitochondrial dysfunction in A549 cells ( Widodo et al, 2022 ). The effect of 3-deoxysappanchalcone (273) on colon cancer cell growth revealed its inhibitory potential on the activity of T-lymphokine-activated killer cell-originated protein kinase (TOPK).…”
Section: Pharmacologymentioning
confidence: 99%